2020
DOI: 10.5194/hess-2020-472
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Simulating the evolution of the topography-climate coupled system

Abstract: Abstract. Landscape evolution models simulate the long-term variation of topography under given rainfall scenarios. In reality, local rainfall is largely affected by topography, implying that surface topography and local climate evolve together. Herein, we develop a numerical simulation model for the evolution of the topography-climate coupled system. We investigate how simulated topography and rain field vary between no-feedback and co-evolution simulations. Co-evolution simulations produced results significa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 41 publications
1
4
0
Order By: Relevance
“…erosion equals tectonic uplift). These results are consistent with those from previous modelling studies (Anders et al, 2008; Goren et al, 2014; Han et al, 2015; Paik & Kim, 2021; Zavala et al, 2020). The results for divide migration for bare soil conditions are also in agreement with results from previous studies (Anders et al, 2008; Bonnet, 2009), in which the windward side of the domain is found to be gentler for low contributing areas (such as those in the divide), and the drainage divide is displaced from the centre of the domain towards the leeward side (Anders et al, 2008; Bonnet, 2009; Giachetta et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…erosion equals tectonic uplift). These results are consistent with those from previous modelling studies (Anders et al, 2008; Goren et al, 2014; Han et al, 2015; Paik & Kim, 2021; Zavala et al, 2020). The results for divide migration for bare soil conditions are also in agreement with results from previous studies (Anders et al, 2008; Bonnet, 2009), in which the windward side of the domain is found to be gentler for low contributing areas (such as those in the divide), and the drainage divide is displaced from the centre of the domain towards the leeward side (Anders et al, 2008; Bonnet, 2009; Giachetta et al, 2014).…”
Section: Discussionsupporting
confidence: 93%
“…Numerical simulations conducted by Goren et al (2014) investigated the effects of orographic controls on landform evolution under constant uplift and no vegetation cover, revealing that windward slopes are longer and gentler than the leeward ones due to the presence of enhanced erosion induced by higher runoff. A key aspect missing from these previous landscape evolution studies is, however, the effect of coevolving landform–vegetation patterns under orographic precipitation conditions, and their possible implications for landform asymmetry (Paik & Kim, 2021; Smith & Bookhagen, 2021; Zavala et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The redistribution of moisture from the oceans towards continental domains governs the global erosion engine. Spatial variability in precipitation and hence in the availability of water or ice as principal agents of erosion controls the shape of landforms (e.g., Ellis et al, 1999;Willett, 1999;Anders et al, 2008;Bonnet, 2009;Menking et al, 2013;Colberg and Anders, 2014;Goren et al, 2014;Chen et al, 2019;Han et al, 2015;Paik and Kim, 2021). However, feedbacks between topography, precipitation, and erosion may even make it difficult to distinguish between cause and effect (Molnar and England, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It seems that the model of Smith and Barstad (2004) (SB model in the following) received the most attention from the landform evolution modeling community among these models. It was adopted by some other authors in the context of co-evolution of topography and climate (e.g., Anders et al, 2008;Han et al, 2015;Paik and Kim, 2021), although the model of Garcia-Castellanos (2007) has some advantages (see Sect. 6).…”
Section: Introductionmentioning
confidence: 99%